TAX STIMULATION OF INVESTMENT ACTIVITY IN RUSSIA - V. Ponkratov; N. Kuznetsov (Вестник университета)
The article considers the problem of tax incentives for investment activity in the Russian Federation in the current economic conditions. It is shown that in crisis economic conditions, with a financial resources deficit, tax incentives are a key mechanism ensuring the implementation of investment programs of natural monopolies and import substitution projects. The objectives of the tax policy are defined and recommendations are formulated to improve a number of taxes in order to stimulate investment in the Russian economy.